1996
DOI: 10.1007/bf02523832
|View full text |Cite
|
Sign up to set email alerts
|

Blood lipid docosahexaenoic and arachidonic acid in term gestation infants fed formulas with high docosahexaenoic acid, low eicosapentaenoic acid fish oil

Abstract: The effect of fish oil high in docosahexaenoic acid (22:6n-3) and low in eicosapentaenoic acid (20:5n-3) in formula on blood lipids and growth of full-term infants was studied. Infants were fed formula with about 15% oleic acid (18:1), 32% linoleic acid (18:2n-6), 4.9% linolenic acid (18:3n-3) and 0, 0.10, or 0.22% 22:6n-3, or 35% 18:1, 20% 18:2n-6, 2.1% 18:3n-3 and 0, 0.11, or 0.24% 22:6n-3 from 3 d to 16 wk of age (n = 16,18,17,21,17,16, respectively). The formulae had < 0.1% 20:5n-3 and no arachidonic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
1
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 26 publications
0
46
1
2
Order By: Relevance
“…However, four of these studies [20][21][22][23] used only indexes such as weight-for-height or BMI-for-height to evaluate adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…However, four of these studies [20][21][22][23] used only indexes such as weight-for-height or BMI-for-height to evaluate adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier observational data have also shown a positive correlation between body weight and post-natal plasma triglyceride ARA (and total n-6 PUFAs) content and an inverse correlation with ALA (Koletzko and Braun, 1991). Since then, three RCTs investigated the effect on growth in term infants, comparing an IF containing added ARA and DHA with an IF containing DHA alone and with a control formula (Auestad et al, 1997;Birch et al, 1998;Makrides et al, 1999), and three studies (Makrides et al, 1995;Innis et al, 1996;Lapillonne et al, 2000) compared an IF containing added DHA with a control formula. None of these studies found any statistically significant differences in growth, although erythrocyte ARA concentrations were observed to be lower in the groups consuming IF with DHA alone than in the groups consuming the control formula.…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
“…It is now well known that the inclusion of DHA in infant formulas increases DHA in a dose-dependent manner in the blood lipids of infants fed formula (Makrides et al 1995;Carlson et al 1996;Innis et al 1996;Birch et al 1998). In addition, some studies (Birch et al 1998(Birch et al , 2000Hoffman et al 2003) have reported that the addition of DHA to infant formulas increases visual and neural system maturation in term-gestation infants who are fed formula from birth or after initial breast-feeding.…”
Section: Pufa In Human Milk and The Breast-fed Infantmentioning
confidence: 99%